Unusual complication of prolonged indwelling urinary catheter - iatrogenic hypospadias - Garg, Gunjan (J Family Med Prim Care, 2016)
Long-time urethral catheterization may be responsible for various complications such as urethral stricture, urethral fracture, urinary tract infections, and hypospadias. Hypospadias is the most common congenital anomaly of male external genitalia. However, urethral catheter-induced iatrogenic hypospadias is a rare entity. In this article, we describe a case of an elderly male who was found to have iatrogenic hypospadias 2 months after urinary catheterization.